2000
DOI: 10.1128/jvi.74.9.4074-4084.2000
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional Influenza Virus RNA Polymerase in the Methylotrophic Yeast Pichia pastoris

Abstract: Influenza virus RNA polymerase with the subunit composition PB1-PB2-PA is a multifunctional enzyme with the activities of both synthesis and cleavage of RNA and is involved in both transcription and replication of the viral genome. In order to produce large amounts of the functional viral RNA polymerase sufficient for analysis of its structure-function relationships, the cDNAs for RNA segments 1, 2, and 3 of influenza virus A/PR/8, each under independent control of the alcohol oxidase gene promoter, were integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…Although NP is essential for in vivo replication of influenza virus RNA (2,14), the presence of NP was not required for the synthesis of short 14-nt transcripts (Fig. 1), confirming previous studies with short RNA templates (12,13,16,22). Recombinant RNA polymerase prepared by our method also required, as expected (7,8,13), both the 5Ј and 3Ј ends of the vRNA promoter for significant transcriptional activity (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Although NP is essential for in vivo replication of influenza virus RNA (2,14), the presence of NP was not required for the synthesis of short 14-nt transcripts (Fig. 1), confirming previous studies with short RNA templates (12,13,16,22). Recombinant RNA polymerase prepared by our method also required, as expected (7,8,13), both the 5Ј and 3Ј ends of the vRNA promoter for significant transcriptional activity (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…3C). A viral polymerase forms a stable complex (1,36,45), and we confirmed that the N-terminal epitopetagged polymerase subunits used in this study are also able to form a complex (Fig. 1).…”
Section: Inhibition Of Ips-1-mediated Induction Of Type I Ifn Throughsupporting
confidence: 66%
“…4). The activity of model vRNA-directed and primer-dependent RNA synthesis by the 3P complex was the highest among those obtained by various methods so far established in this laboratory (18,23,38,41).…”
Section: Discussionmentioning
confidence: 75%
“…To overcome the above failures to obtain large amounts of the functional RNA polymerase in RNA-free form, we have developed an expression system of functional form of influenza virus RNA polymerase in methylotrophic yeast Pichia pastoris (41), but the purification of RNA polymerase without contamination of endogenous nucleases was difficult. Here we succeeded in expressing all three P proteins simultaneously in insect cells after coinfection with three species of the recombinant baculovirus, each coding for PB1, PB2, and H-PA.…”
Section: Discussionmentioning
confidence: 99%